Effects of a programme of multifactorial home visits on falls and mobility impairments in elderly people at risk: randomised controlled trial. Issue 7267 (21st October 2000) - van Haastregt, Jolanda C M; Diederiks, Jos P M; van Rossum, Erik; de Witte, Luc P; Voorhoeve, Peter M; Crebolder, Harry F J M
Abstract: Objective: To evaluate whether a programme of multifactorial home visits reduces falls and impairments in mobility in elderly people living in the community. Design: Randomised controlled trial with 18 months of follow up. Setting: Six general practices in Hoensbroek, the Netherlands. Participants: 316 people aged 70 and over living in the community, with moderate impairments in mobility or a history of recent falls. Intervention: Five home visits by a community nurse over a period of one year. Visits consisted of screening for medical, environmental, and behavioural factors causing falls and impairments in mobility, followed by specific advice, referrals, and other actions aimed at dealing with the observed hazards. Main outcome measures: Falls and impairments in mobility. Results: No differences were found in falls and mobility outcomes between the intervention and usual care groups. Conclusion: Multifactorial home visits had no effects on falls and impairments in mobility in elderly people at risk who were living in the community. Because falls and impairments in mobility remain a serious problem among elderly people, alternative strategies should be developed and evaluated.